MANAJEMEN PENERAPAN KURIKULUM 2013 DI SEKOLAH DASAR - Ernawatie (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
The purpose of this study was to describe the Management of Implementation of the 2013 Curriculum for Basic Education, in terms of: (1) planning; (2) implementation; and (3) supervision. This study used a qualitative approach with case study design. Determination of informants is done by purposive sampling technique. The data collection techniques used are: (1) observation, (2) interviews, and (3) documentation. Data analysis was carried out by adopting an interactive pattern which included data condensation, data presentation and drawing conclusions. Checking the credibility of the data is done by using triangulation of sources and techniques/methods. Confirmability checks are used to see that the results of the research conducted indicate a research process in the field. The results showed that the management of the implementation of the 2013 curriculum for basic education was included in the fairly good category and carried out in accordance with the provisions of the applicable laws; although the implementation still needs further development.